Research and development of a preliminary South African voluntary carbon standard for landscape restoration projects - Curran, Patrick (Rhodes University, Faculty of Science, Department of Environmental Science, 2012)
The mandatory and voluntary carbon markets have both developed around the increasing trade of carbon offsets. In order to add legitimacy to an otherwise intangible commodity there has been a rise in the development of third party carbon certification standards, particularly in the voluntary market. These standards aim to provide independent, third party certification to projects that are developed specifically to generate and sell carbon offsets. South Africa has the opportunity to engage with these markets, but current participation in and certification of projects is sluggish. These projects have not taken off mainly due to the high transaction costs and lag times surrounding the current certification of projects', complex baseline methodologies, accounting uncertainty and the often bureaucratic systems surrounding the current voluntary carbon certification standards and methodologies. In order to overcome these pitfalls this project aimed to address these challenges through initiating the development of a preliminary South African voluntary carbon standard. This was done by: a) undertaking a critical assessment of the development of current carbon markets, with a particular focus on voluntary markets and third party certification, b) critically analysing the current voluntary carbon certification standards for best practices, pitfalls and weaknesses. To provide a better understanding of the historical development of voluntary certification standards, various established certification standards were evaluated, including the Forestry Stewardship Council (FSC), Marine Stewardship Council (MSC) and ISO 14000 standards. This analysis focussed on the challenges they faced in acceptance and in particular how they have managed to operationalize sustainable development within the certification process. In order to explicitly ensure the incorporation of a sustainable development assessment of projects under the proposed standard, an expert workshop was held with 14 experts from a wide variety of disciplines. These experts identified the crucial sustainable development challenges facing South Africa. They identified 12 sub-themes and 44 indicators that could be used to measure and incorporate sustainable development indicators into the certification process. These were then further developed through using the 'Input "“ Output "“ Outcome "“ Impact' framework model which allowed the indicators to be organised and understood and thus practical. The analysis of the voluntary certification standards and the development of the sustainable development indicator framework were ultimately incorporated into the development of the proposed South African voluntary carbon standard. The key approach to this standard is the incorporation and focus of the proposed standard to ensuring the generation of net SD benefits and placing them at the same level as carbon within the project design and development, validation and verification process. The full and effective integration of these has been missing within current fully fledged voluntary carbon standards, as they often rely on a mixture of project design standards to achieve this. Offering the inclusion of all components into one standard, specifically designed for South Africa, will not only assure SD credentials but also increase transparency and understanding, and reduce costs. This thesis allowed for the development of innovative new ideas and process focussed specifically at including and mainstreaming South Africa's developmental challenges into the certification process. This is the hoped that the standard will effectively certify South African based landscape restoration projects, but also decrease costs and increase efficiencies in order to encourage the development of these projects. This preliminary standard not only aims to incorporate and address all the issues identified but also has the end goal of acting as the basis for future debate and development surrounding a potential South African voluntary carbon certification standard.
Keywords: Carbon -- Environmental aspects -- Research -- South Africa; Carbon -- Standards -- Research; Restoration ecology -- Research -- South Africa; Environmental sciences -- Research